IMPLEMENTASI WAKAF TUNAI DALAM UU NO 41 TAHUN 2004 DI BANK MUAMALAT INDONESIA LAMPUNG TIMUR - Siti Fatimah (AS-SALAM, 2015)
Waqf is one instrument in Islamic economy that aims to achieve the objectives of Islamic economics is to realize a prosperous life. Endowments are still seen as practice for the rich, because the payment is identical to the endowments of land and buildings. Cash Waqf has accommodated formal judicial since the enactment of Law No. 41 of 2004. While the technical rules of cash endowments, newly published in 2009 Bank Muamalat Indonesia readiness so as LKS-PWU and the Ministry of Religious Affairs in the implementation of cash waqf lampungtimur interesting to study. Related to the bank’s readiness Muamalat lampung east, the principle has been prepared by the circular of Bank Muamalat operations center. However unfortunate lampung east bank Muamalat not socialize and publicize that they are as LKS-PWU. While the readiness of the Ministry of Religious lampungTimur very helpful terlaksanyanya cash waqf, where they have not received and know the Minister of Religious Affairs Regulation No. 4 of 2009 on Administration of Registration of Cash Waqf. Therefore socialization cash endowments in order its implementation is very important.